Heterozygosity of murine Crkl does not recapitulate behavioral dimensions of human 22q11.2 hemizygosity - Yamauchi, Takahira (Genes Brain Behav, 2020)
Deletions in 22q11.2 human chromosome are known to be associated with psychiatric disorders, such as intellectual disability, schizophrenia, autism spectrum disorder, and anxiety disorders. This copy number variation includes a 3.0 Mb deletion and a nested proximal 1.5 Mb hemizygous deletion in the same region. Evidence indicates that the distal 22q11.2 region outside the nested 1.5 Mb deletion also might be contributory in humans. However, the precise genetic architecture within the distal region responsible for psychiatric disorders remains unclear, and this issue cannot be experimentally evaluated beyond the correlation in humans. As CRKL (CRK-like Proto-Oncogene, Adaptor Protein) is one of the genes encoded in the distal 22q11.2 segment and its homozygous deletion causes physical phenotypes of 22q11.2 hemizygous deletion, we tested the hypothesis that its murine homolog Crkl contributes to behavioral phenotypes relevant to psychiatric disorders in mice. Congenic Crkl heterozygosity reduced thigmotaxis, an anxiety-related behavior, in an inescapable open field, but had no apparent effect on social interaction, spontaneous alternation in a T-maze, anxiety-like behavior in an elevated plus maze, or motor activity in an open field. Our data indicate that the heterozygosity of murine Crkl does not recapitulate social deficits, working memory deficits, repetitive behavior traits or hyperactivity of human 22q11.2 hemizygous deletion. Moreover, while 22q11.2 hemizygous deletion is associated with high levels of phobia and anxiety in humans, our data suggest that Crkl heterozygosity rather acts as a protective factor for phobia-like behavior in an open field.